A comparison between two different finishing systems for swine - Rocha, Mércia de Andrade; Meneguelli, Carlos Alberto; Moreira, Amaury Cavalcanti de Souza; Alvarenga, Júlio Calvelli; Lima, Therezinha de Almeida Oliveira (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted at the Instituto de Pesquisa Agronecuária do Centro-Sul (IPEACS), Rio de Janeiro, Brazil, to compare two systems of finishing swine. One group was fattened on pasture, while the other was raised in confinement. Twenty-four weaned Hampshire pigs were used in a randomized block design four replications per treatment. The animals raised in pasture took fewer days to reach a market weight of 90 kg (171 days) than raised in confinement (187 days). Total ration consumed was significantly higher (P < .01) for the group on pasture. Pigs fed on pasture were significantly (P < .05) more efficient at converting feed than those in confinement. Although the pasture fed pigs tended to gain more rapidly, this difference was not statistically significant.